Implementation of road dust resuspension in air quality simulations of particulate matter in Madrid (Spain) - de la Paz, David; Borge, Rafael; Vedrenne, Michel; Lumbreras, Julio; Amato, Fulvio; Karanasiou, Angeliki; Boldo, Elena; Moreno, Teresa (Frontiers in Environmental Science, 2015)
An evaluation of the concentration levels of Particulate Matter (PM) was carried out in Madrid (Spain) by introducing the emissions from road dust resuspension. Road dust resuspension emission factors (EF) for different types of vehicles were calculated from EPA-AP42, a global resuspension factor of 0.097 g veh-1 km-1 as described in Amato et al. (2010) and a rain-dependent correction factor. With these resuspension EFs, a simulation at street canyon level was performed with the OSPM model without rainfall. Subsequently, a simulation using the CMAQ model was implemented adding resuspension emissions affected by the rain. These data were compared with monitored data obtained from air quality stations. OSPM model simulations with resuspension EFs but without the effect of rainfall improve the PM estimates in about 20 µg m-3 compared to the simulation with default EFs. Total emissions were calculated by adding the emissions estimated with resuspension EFs to the default PM emissions to be used by CMAQ. For the study in the Madrid Area, resuspension emissions are approximately of the same order of magnitude as inventoried emissions. On a monthly scale, rain effects are negligible for resuspension emissions due to the dry weather conditions of Spain. With the exception of April and May, the decrease in resuspension emissions is not greater than 3%. The predicted PM10 concentration increases up to 9 µg m-3 on annual average for each station compared to the same scenario without resuspension. However in both cases, PM10 estimates with resuspension are still underestimating observations. It should be noted that although that accounting for resuspension improves the quality of model predictions, other PM sources (e.g. Saharan dust) were not considered in this study.